If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -2) = 5(x + 3) Reorder the terms: x(-2 + x) = 5(x + 3) (-2 * x + x * x) = 5(x + 3) (-2x + x2) = 5(x + 3) Reorder the terms: -2x + x2 = 5(3 + x) -2x + x2 = (3 * 5 + x * 5) -2x + x2 = (15 + 5x) Solving -2x + x2 = 15 + 5x Solving for variable 'x'. Reorder the terms: -15 + -2x + -5x + x2 = 15 + 5x + -15 + -5x Combine like terms: -2x + -5x = -7x -15 + -7x + x2 = 15 + 5x + -15 + -5x Reorder the terms: -15 + -7x + x2 = 15 + -15 + 5x + -5x Combine like terms: 15 + -15 = 0 -15 + -7x + x2 = 0 + 5x + -5x -15 + -7x + x2 = 5x + -5x Combine like terms: 5x + -5x = 0 -15 + -7x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '15' to each side of the equation. -15 + -7x + 15 + x2 = 0 + 15 Reorder the terms: -15 + 15 + -7x + x2 = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -7x + x2 = 0 + 15 -7x + x2 = 0 + 15 Combine like terms: 0 + 15 = 15 -7x + x2 = 15 The x term is -7x. Take half its coefficient (-3.5). Square it (12.25) and add it to both sides. Add '12.25' to each side of the equation. -7x + 12.25 + x2 = 15 + 12.25 Reorder the terms: 12.25 + -7x + x2 = 15 + 12.25 Combine like terms: 15 + 12.25 = 27.25 12.25 + -7x + x2 = 27.25 Factor a perfect square on the left side: (x + -3.5)(x + -3.5) = 27.25 Calculate the square root of the right side: 5.220153254 Break this problem into two subproblems by setting (x + -3.5) equal to 5.220153254 and -5.220153254.Subproblem 1
x + -3.5 = 5.220153254 Simplifying x + -3.5 = 5.220153254 Reorder the terms: -3.5 + x = 5.220153254 Solving -3.5 + x = 5.220153254 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + x = 5.220153254 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + x = 5.220153254 + 3.5 x = 5.220153254 + 3.5 Combine like terms: 5.220153254 + 3.5 = 8.720153254 x = 8.720153254 Simplifying x = 8.720153254Subproblem 2
x + -3.5 = -5.220153254 Simplifying x + -3.5 = -5.220153254 Reorder the terms: -3.5 + x = -5.220153254 Solving -3.5 + x = -5.220153254 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + x = -5.220153254 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + x = -5.220153254 + 3.5 x = -5.220153254 + 3.5 Combine like terms: -5.220153254 + 3.5 = -1.720153254 x = -1.720153254 Simplifying x = -1.720153254Solution
The solution to the problem is based on the solutions from the subproblems. x = {8.720153254, -1.720153254}
| 3x-88=28 | | 12y^2-11y+2=0 | | -8(3x+7)=136 | | 4.6=9.1-0.5x | | 101.5=j-82.8 | | 25m^2-40mn+16n^2= | | x^2+y^2+14x+12y+21=0 | | -5x(2x+7xy)+7xy-4x(xy+3y)= | | p^6-q^6=0 | | 8*24+x=432 | | 3x+7=-8+3x | | 125(n-4)=375 | | -5(x+2)=3(-2x+1) | | -5y(y+4)=17+3y | | -6t-0.8=5.2 | | 63b^2+45b=0 | | 3(x-1)+5x-6+x+x+x=x | | 6+2+c=9 | | 5+6x+7x=109 | | x^2+0b-81=0 | | -5x-5=0 | | 2(x+4)-(3x-14)=7x-2 | | -2[-2(3+-2)]= | | -3d-(-42)=12 | | -3.1=-31a | | -2[-2(3-2)]= | | -1*5*z+12=18 | | 4(2x-1)=-a+25 | | 7x^2+14x+0=0 | | 2n+5=4(n+2) | | 18y-19=17+18y | | 1+y+2(3)=3 |